Niacin alters ruminal microbial composition and metabolites in sheep fed a high-concentrate diet - Cheng, Zhiqiang; Liu, Jiancheng; Yu, Yingying; Liu, Wentao; Li, Xiaobin; Li, Fengming; Zang, Changjiang; Yang, Kailun (Frontiers in Veterinary Science, 2025)
This study aimed to investigate the effects of niacin supplementation to a high-concentrate diet (ratio of concentrate supplement to forage = 70:30) on the growth performance, rumen fermentation, rumen microbiota, and metabolomics of sheep. Twelve sheep were randomly divided into two groups: (1) a control group (CON, n = 6) fed a basal diet and (2) a niacin group (NA, n = 6) fed a basal diet supplemented with 130 mg/day niacin for 35 days: days 1–14 were the adaptation period, days 15–35 were the experiment period. On days 15 and 35 of the experiment period, all trial sheep were weighed before the morning feed (07:30 am). Ruminal fluid samples were collected from all trial sheep on days 34 and 35. The results showed that (1) the dry matter feed intake of the NA group was higher than that of the CON group (p < 0.05). (2) The ruminal pH of the NA was significantly higher than that of the CON group at 3, 5, and 7 h after feeding (p < 0.01). The concentrations of NH3-N (p < 0.01), propionate (p < 0.01), and butyrate (p < 0.05) in the NA group were significantly higher than those in the CON group. (3) Compared to the CON group, the ruminal pyruvate content in the NA group was significantly increased at 0 h before feeding (p < 0.05), and lactic acid (p < 0.05) was significantly decreased at 1 and 3 h after feeding, lactate dehydrogenase activities was significantly decreased (p < 0.01) at 3 and 5 h after feeding. (4) The number of specific operational taxonomic units (OTUs) in the CON and NA groups were 26 and 37, respectively, for a total of 1,178 OTUs; principal coordinate analysis (R2 = 0.172, p-value = 0.007) and non-metric multidimensional scaling (stress = 0.1646) results showed that the two groups of samples were significantly separated. (5) The species distribution bar graph shows that at the phylum level, the relative abundances of Bacteroidetes, Firmicutes, and Proteobacteria were 43.70, 36.25, and 12.77%, respectively. (6) Orthogonal projection to latent structure-discriminant analysis results showed that the two groups of samples were clearly separated in the positive and negative ionization modes, with R2Y and Q2Y values of 0.705, 0.857, 0.695, and 0.28, respectively. There were 72 metabolic pathways, mainly citric acid cycle, pyruvate metabolism, and cysteine and methionine metabolism. (7) Correlation analysis showed that a number of microorganisms (such as Succinivibrio and Prevotella) and differential metabolites (such as L-malic acid, propionic acid, succinic acid, and pyruvic acid) participated in tricarboxylic acid cycle metabolism. In summary, supplementing niacin to high-concentrate diets can significantly improve the growth performance of sheep, improve rumen fermentation and the rumen microbial community structure, and affect rumen metabolites, thus alleviating the symptoms of rumen acidosis.